Comparison of QFT-Plus and QFT-GIT tests for diagnosis of M. tuberculosis infection in immunocompetent Korean subjects - Hong, Ji Young; Park, So Yeong; Kim, Ahreum; Cho, Sang-Nae; Hur, Yun-Gyoung (Journal of thoracic disease, 2019)
QFT-Plus is a recently developed next-generation QuantiFERON-TB Gold In-Tube (QFT-GIT) test. Unlike the QFT-GIT test, it includes a TB2 antigen tube with peptides that may stimulate CD8+ T cells. This study evaluated the diagnostic performance of QFT-Plus and compared it with that of QFT-GIT. QFT-Plus and QFT-GIT tests were performed in 33 patients with active tuberculosis (TB) and 57 healthy controls including subjects with latent TB infection (LTBI). Positivity and negativity of IFN-γ responses were compared between tests, and total concordance of the outcome was analyzed. Positive and negative outcomes of QFT-Plus and QFT-GIT tests showed substantial agreement (91.1%, kappa=0.8). The sensitivity and the specificity of QFT-Plus (93.9% sensitivity, 92.6% specificity) were similar with those of QFT-GIT (93.9% sensitivity, 100% specificity). Of eight discordant results, five (5.56%) and three (3.3%) were positive in QFT-GIT alone and QFT-plus alone, respectively. Reactivity in the TB2 tube contributes to the difference between QFT-GIT and QFT-Plus. Median IFN-γ production in TB2 (10.0 IU/mL in TB, 3.850 IU/mL in LTBI, P=0.001) is significantly higher in the TB group than the LTBI group. The QFT-Plus did not clearly discriminate between active TB and latent TB, although it showed significantly lower IFN-γ concentrations compared with the QFT-GIT in individuals with LTBI (3.850 7.205 IU/mL). Similar accuracy of detecting infection was observed for QFT-Plus and QFT-GIT tests in immunocompetent patients and healthy controls, including those with LTBI. Improved efficacy for identifying infection was not found with the QFT-Plus, but further studies in a larger population may confirm the clinical significance of positive response in the TB2 tube of QFT-Plus.